Tenogenesis of Decellularized Porcine Achilles Tendon Matrix Reseeded with Human Tenocytes in the Nude Mice Xenograft Model - Lohan, Anke (Int J Mol Sci, 2018)
Cultivation of autologous human tenocytes in a cell-free xenogenic extracellular tendon matrix (xECM) could present an approach for tendon reconstruction. The aim of this study was to achieve tendon-like tissue formation by implanting decellularized porcine Achilles tendons recellularized with human hamstring tendon-derived tenocytes into nude mice. The structure of decellularized xECM was histologically monitored before being dynamically reseeded with human tenocytes. After 6–12 weeks in vivo, construct quality was monitored using macroscopical and histological scoring systems, vitality assay and quantitative DNA and glycosaminoglycan (GAG) assays. For comparison to tendon xECM, a synthetic polyglycolic acid (PGA) polymer was implanted in a similar manner. Despite decellularized xECM lost some GAGs and structure, it could be recellularized in vitro with human tenocytes, but the cell distribution remained inhomogeneous, with accumulations at the margins of the constructs. In vivo, the xECM constructs revealed in contrast to the PGA no altered size, no inflammation and encapsulation and a more homogeneous cell distribution. xECM reseeded with tenocytes showed superior histological quality than cell-free implanted constructs and contained surviving human cells. Their DNA content after six and 12 weeks in vivo resembled that of native tendon and xECM recellularized in vitro. Results suggest that reseeded decellularized xECM formed a tendon-like tissue in vivo.